2010
DOI: 10.1007/s11240-010-9852-z
|View full text |Cite
|
Sign up to set email alerts
|

Anther culture for haploid and doubled haploid production

Abstract: Haploids are plants with a gametophytic chromosome number and doubled haploids are haploids that have undergone chromosome duplication. The production of haploids and doubled haploids (DHs) through gametic embryogenesis allows a single-step development of complete homozygous lines from heterozygous parents, shortening the time required to produce homozygous plants in comparison with the conventional breeding methods that employ several generations of selfing. The production of haploids and DHs provides a parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
191
0
44

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(236 citation statements)
references
References 199 publications
(222 reference statements)
1
191
0
44
Order By: Relevance
“…With DH production systems established, homozygous lines can be achieved in one generation, which would allow to reduce the time and cost of cultivar development (Dunwell 2010;Ferrie and Caswell 2010;Germanà 2011). The system has been effectively used in barley, wheat (Jauhar et al 2009;Ferrie and Caswell 2010), maize (Smith et al 2008;Chang and Coe 2009), and various Brassica species (Belmonte et al 2006;Fang et al 2006;Zhang et al 2008;Takahira et al 2011;Winarto and Teixeira da Silva 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With DH production systems established, homozygous lines can be achieved in one generation, which would allow to reduce the time and cost of cultivar development (Dunwell 2010;Ferrie and Caswell 2010;Germanà 2011). The system has been effectively used in barley, wheat (Jauhar et al 2009;Ferrie and Caswell 2010), maize (Smith et al 2008;Chang and Coe 2009), and various Brassica species (Belmonte et al 2006;Fang et al 2006;Zhang et al 2008;Takahira et al 2011;Winarto and Teixeira da Silva 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For some species, there is a high percentage of spontaneous chromosome doubling, which results in homozygous DH plants. If spontaneous doubling does not occur, or occurs at a low frequency, the haploid plants need to be treated with a doubling agent, such as colchicine, oryzalin, and trifluralin (Maluszynski et al 2003;Castillo et al 2009;Germanà 2011;Mohammadi et al 2012). Cytogenetic analysis has shown that there were high rate of spontaneous diploidization in carrot anther culture (Zhuang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, microspores and MDEs can be used for mutagenesis and in vitro selection (Albrecht et al 1995;Barro et al 2001;Ferrie et al 2008;McClinchey and Kott 2008) and it is possible to utilize microspores for genetic transformation (Guerche et al 1987;Fukuoka et al 1998;Nehlin et al 2000;Dormann et al 2001). The main advantage of androgenesis is, that traits can be fixed in one generation rather than after multiple selfpollinated generations (Dunwell 2010;Ferrie and Caswell 2011;Germanà 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gametic embryogenesis, which allows the single-step development of complete homozygous lines from heterozygous parents, has already had a huge impact on the agricultural systems of many agronomically important crops, representing an integral part in their breeding programs (Germanà 2011a(Germanà , 2011b. To induce gametic embryogenesis, it is necessary to switch the gametic cells from their normal developmental pathway toward a sporophytic pathway.…”
Section: Introductionmentioning
confidence: 99%